Omental incarceration secondary to uterine perforation after dilatation curettage: Conservative approach in sub‐saharan Africa - Ozer Birge; Ilkan Kayar; Fatthy Bello (Clinical Case Reports)
Key Clinical Message Complications of uterine perforation and herniation of intra‐abdominal organs into the perforated area may occur after gynecological operations. They can be treated with a conservative approach, especially in cases whose vital signs are stable, laboratory values are within normal limits and their general condition is suitable. We aim to present the conservative treatment without using surgical and medical methods as it is the first case in the literature. Abstract Uterine perforation is a rare but potentially serious complication of curettage for gynecologic or obstetric reasons especially during and after operative procedures and the application of intrauterine contraceptive devices. The incidence of uterine perforation during gynecological operations is between 0.002–1.7. A 30‐year‐old multiparous case with a 7‐week 4‐day pregnancy was diagnosed with incomplete abortion at an external center due to vaginal bleeding. The case underwent suction curettage. After 24 h, revision suction curettage was performed due to the finding of rest in the endometrium during the ultrasonographic control, and the case was diagnosed with uterine perforation and omental herniation due to this. We highlighted the importance of a thorough gynecological assessment following a dilated suction curettage (D&C) procedure that includes a careful clinical examination and a detailed ultrasound evaluation.